Determinazione e libertà in Nicolai Hartmann - Vaccaro, Giovambattista (Filosofia Morale/Moral Philosophy, 2024)
Some recent interpreters of Hartmann stress the importance of the modal category of effectiveness in his ontology and disregard the modal category of possibility. Through an analysis of the volume two of Hartmann’s ontology this essay aims to show that such interpretation is partial, because possibility comes into the real world from the ideal world of the moral values through the free action of human being.